EFFECTIVE COMMUNICATION BRIDGE BETWEEN TRADITION AND MODERNITY: PUBLIC RELATIONS OF THE AL IHSAN ISLAMIC BOARDING SCHOOL, PASER REGENCY - Andriani, Rina (PROCEEDING OF INTERNATIONAL CONFERENCE ON EDUCATION, SOCIETY AND HUMANITY, 2024)
Al Ihsan Islamic Boarding School faces the challenge of bridging the strong Islamic boarding school tradition with religious values and the needs of modernity in the digital era. As the spearhead of communication, Public Relations has a strategic role in creating synergy between tradition and modernity through an effective communication approach. This research aims to analyze the Public Relations strategy of the Al Ihsan Islamic Boarding School in building a communication bridge between these two dimensions. The method used is qualitative research with interview techniques, observation and documentation. The research results show that Al Ihsan Islamic Boarding School Public Relations implements strategies based on traditional values, such as honesty, trustworthiness and friendship, combined with modern communication technology, such as social media and websites. This collaboration produces communication that is relevant to modern society without losing the Islamic boarding school's identity. The conclusion of this research confirms that an effective communication bridge between tradition and modernity can be realized through innovation based on Islamic boarding school values, thereby strengthening the image of Islamic boarding schools in the eyes of the public.